2011
DOI: 10.1080/19440049.2011.641163
|View full text |Cite
|
Sign up to set email alerts
|

Application of an untargeted metabolomics approach for the identification of compounds that may be responsible for observed differential effects in chickens fed an organic and a conventional diet

Abstract: boom. Application of untargeted metabolomics approach for identification of compounds that may be responsible for observed differential effects in chickens fed an organic and a conventional diet. Food Additives and Contaminants, 2012, pp.1. <10.1080/19440049.2011 The aim of this study was to apply an untargeted NMR and LC-MS based metabolomics approach to detect potential differences between an organically and a conventionally produced feed, that caused statistically significant differences in growth, in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Later RIKILT conducted research in which untargeted as well as targeted were measured. In this study, the substance N, N0-diferuloyl putrescine (DFP) was found in corn, which was different in organic and conventional corn (Ruiz-Aracama et al, 2012). Unfortunately not much was known about that substance, but it could be a research topic for follow-up research.…”
Section: Original Research and Summary Of Resultsmentioning
confidence: 86%
“…Later RIKILT conducted research in which untargeted as well as targeted were measured. In this study, the substance N, N0-diferuloyl putrescine (DFP) was found in corn, which was different in organic and conventional corn (Ruiz-Aracama et al, 2012). Unfortunately not much was known about that substance, but it could be a research topic for follow-up research.…”
Section: Original Research and Summary Of Resultsmentioning
confidence: 86%
“…NMR, mainly used to analyze polar metabolites, permits the detection of a broad scope of analytes within a single run. However, NMR typically exhibits disadvantages such as lower sensitivity compared to GC‐MS and LC‐MS (Lei et al., 2011 ; Ruiz‐Aracama et al., 2012 ).…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…Later is door RIKILT nog onderzoek gedaan, waarbij naast targeted ook untargeted is gemeten. Hierbij is er in mais de stof N,N0-diferuloylputrescine (DFP) gevonden die verschillend was in biologisch en gangbaar(Ruiz-Aracama et al, 2012). Van die stof was helaas niet zoveel bekend maar het zou een onderzoeksonderwerp kunnen zijn voor vervolgonderzoek.…”
unclassified